High discrepancies in the mortality of hospitalized patients with COVID-19 in the two most economically important states in Brazil - Vitor Barreto Paravidino; Rosely Sichieri; Danilo Cosme Klein Gomes; Gulnar Azevedo e Silva (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2021)
ABSTRACT: Objective: The aim of this study was to compare the proportion of deaths among hospitalized cases of COVID-19 in São Paulo and Rio de Janeiro, stratified by private and public services. Methods: Hospitalization data for severe acute respiratory syndrome (SARS) were obtained using the SIVEP-Gripe Database. All hospitalized adults who were diagnosed as COVID-19 or unspecified SARS, between January and December 2020, were included in the analysis. Logistic regression models were fitted to evaluate the risk of death between Rio de Janeiro and São Paulo, adjusted for age, sex, and comorbidities. Results: A total of 388,657 hospital registers for Rio de Janeiro and São Paulo (91,532 and 297,125, respectively) were analyzed. Missing data are frequent in the database and it was greater in Rio de Janeiro, at the state and capital levels. Adjusting for confounders, the odds ratio of dying by COVID-19, comparing the state of Rio de Janeiro with São Paulo, was 2.51 in the private hospitals and 2.29 in the public ones. For the capitals, the scenario is worse. The lethality among hospitalized patients with COVID-19 is at least twice in Rio de Janeiro than São Paulo, both at the states and capitals. The public or private services showed important differences, with odds ratios of 2.74 and 3.46, respectively. Conclusion: It appears that the worst governance in the health sector in Rio de Janeiro, more than lack of resources, explains the excess mortality of hospitalized COVID-19 patients in Rio de Janeiro.